Sustainable Learning Through Problem Based Learning with Socioscientific Issue: An Analysis of Science Literacyand scientific attitudes of high school students - Haka, Nukhbatul Bidayati; Sulistyawati, Ayu; Oktafiani, Raicha; Supriyadi, Supriyadi; Jamaludin, Didi Nur (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The research aimed to analyse the effect of Problem Based Learning model with Socioscientific Issue on science literacy and scientific attitude of high school students. This research was conducted in public high school in Kalianda. The research design used was Quasi-Experiment with Pretest- Posttest Control Group method. Cluster Random Sampling technique was used to get the sample of Class XI. The sample consisted of Class XI.10 totalling 35 students as the control class while Class XI. 5 class totalling 36 students as the experimental class. The type of data is quantitative. Tests and questionnaires were used to collect data. Based on the Pretest-Posttest results, the experimental class met the ‘High’ category with an N-gain score of 0.804, while the control class met the ‘Medium’ category with an N-Gain score of 0.650. Independent sample t-test was used to test the hypothesis, with a Sig (2-tailed) value of 0.000 <0.05. The conclusion of this study is that science literacy and scientific attitudes of high school students are influenced by the Problem Based Learning model with Socioscientific Issue. Therefore, it is expected that this research is useful in improving the scientific literacy and attitude of high school students.Keywords: Problem Based Learning, Socioscientific Issue, Science Literacy, Scientific Attitude.DOI: 10.23960/jppk.v13i3.31848